2011
DOI: 10.1115/1.4003292
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Calcium Chloride Solar Storage: Concept and Analysis

Abstract: Aqueous calcium chloride has a number of potential advantages as a compact and long-term solar .storage medium compared with sensibly heated water. The combination of sensible and chemical binding energy of the liquid desiccant provides higher energy densities and lower thermal losses, as well as a temperature lift during discharge via an absorption heat pump. Calcium chloride is an excellent choice among desiccant materials because it is relatively inexpensive, nontoxic, and environmentally safe. This paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…All transient experiments as well as a computational fluid dynamic study [Quinnell et al, 2011 andQuinnell andDavidson, 2012c] show that the density interfaces remain stable and the natural convection flows are confined to regions of uniform CaCl 2 mass fraction. Representative data are provided for an experiment in which Ra is of order 10 9 , N is of order 4, Le = 404, and a = 0.5.…”
Section: Ld Storage Tankmentioning
confidence: 98%
See 2 more Smart Citations
“…All transient experiments as well as a computational fluid dynamic study [Quinnell et al, 2011 andQuinnell andDavidson, 2012c] show that the density interfaces remain stable and the natural convection flows are confined to regions of uniform CaCl 2 mass fraction. Representative data are provided for an experiment in which Ra is of order 10 9 , N is of order 4, Le = 404, and a = 0.5.…”
Section: Ld Storage Tankmentioning
confidence: 98%
“…Faster heat and mass transfer rates are possible with liquid absorption. Materials recently investigated include aqueous solutions of CaCl 2 [Quinnell et al, 2011], LiCl [Bales, 2006], NaOH , and KOH [Hui et al, 2011]. Hui et al compare absorption materials for use in low pressure (1.2 -4.2 kPa) absorption cycles and have reported theoretical material energy densities up to 476 kWh/m 3 [Hui et al, 2011], as shown in …”
Section: Liquid Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…when the cooling/dehumidification demand is needed to meet, the concentrated solution is pumped to the absorber, driving the cycle without any further heat needed; once the process is completed, the obtained dilute solution is stored in the dilute solution tank. Sometimes, in reality, one tank was used instead of using two tanks, where the strong and weak solutions were mixed or separated by buoyancy [110]. The energy storage capacity of a liquid desiccant, SC, is defined as [111]:…”
Section: Thermo-chemical Energy Storage Capacitymentioning
confidence: 99%
“…Solar energy is stored in a liquid CaCl 2 volume by heating the solution and vaporizing H 2 O. Energy is extracted as water is reabsorbed and/or the solution is cooled (142). The energy density of the material, which is dependent on how the tank is discharged, is 106 kWh/m 3 , similar to that of LiCl for the same operating parameters (98).…”
Section: Liquid Absorption Materialsmentioning
confidence: 99%